Physicochemical interaction mechanism between nanoparticles and tetrasaccharides (stachyose) during freeze-drying - Kamiya, Seitaro; Nakashima, Kenichiro (Drug development and industrial pharmacy, 2017)
Nanoparticle suspensions are thermodynamically unstable and subject to aggregation. Freeze-drying on addition of saccharides is a useful method for preventing aggregation. In the present study, tetrasaccharides (stachyose) was employed as an additive. In addition, we hypothesize the interactive mechanism between stachyose and the nanoparticles during freeze-drying for the first time. The mean particle size of the rehydrated freeze-dried stachyose-containing nanoparticles (104.7 nm) was similar to the initial particle size before freeze-drying (76.8 nm), indicating that the particle size had been maintained. The mean particle size of the rehydrated normal-dried stachyose-containing nanoparticles was 222.2 nm. The powder X-ray diffraction of the freeze-dried stachyose-containing nanoparticles revealed a halo pattern. The powder X-ray diffraction of the normally dried stachyose-containing nanoparticles produced mainly a halo pattern and a partial peak. These results suggest an interaction between the nanoparticles and stachyose, and that this relationship depends on whether the mixture is freeze-dried or dried normally. In the case of normal drying, although most molecules cannot move rapidly thereby settling irregularly, some stachyose molecules can arrange regularly leading to some degree of crystallization and potentially some aggregation. In contrast, during freeze-drying, the moisture sublimed, while the stachyose molecules and nanoparticles were immobilized in the ice. After sublimation, stachyose remained in the space occupied by water and played the role of a buffer material, thus preventing aggregation.